Sex Psycoeducation To Prevent Sexual Abuse In Children - Sitti Anggraini; Florensia Nei; Maria Kami; Maria Vinsensiana Hediana Mbere; Yasinta Roman; Renata Lodhu Rais (Peneliti Teknologi Teknik Indonesia, 2023)
Cases of sexual violence against children always increase every year, seeing this, to reduce the rate of growth in the occurrence of sexual violence, one of the efforts made is to carry out psychoeducation for elementary school students with the theme of body parts that can and cannot be touched by people. other. This aims to provide understanding to children that not all parts of their bodies can be touched by other people, even if it is their own parents. Before carrying out psychoeducation, as a form of community service, direct observations and interviews are carried out with the school principal, guardian. classes and to student representatives regarding knowledge about sexual violence that occurs in schools. The results of the preetest carried out before sexual psychoeducation were 4.9 posttest, so the results obtained were preetest 4.9 < posttest 9.53, meaning that there was an increase in knowledge (cognitive) in children about how to deal with sexual violence in children.